2003
DOI: 10.1002/jbm.b.10077
|View full text |Cite
|
Sign up to set email alerts
|

The effects of lubricant composition on in vitro wear testing of polymeric acetabular components

Abstract: Lubricant composition is known to affect in vitro (simulator) wear of polymeric acetabular components. Clinical acetabular components, fabricated from both ultrahigh molecular weight polyethylene (UHMWPE) and polytetrafluoroethylene (PTFE), were tested against cobalt-chromium 32-mm ball heads, with the use of various lubricants, with different compositions and concentrations of bovine and calf serum as well as hyaluronic acid, in tests which lasted one million cycles. The type of proteins and their relative co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
140
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(151 citation statements)
references
References 27 publications
6
140
0
1
Order By: Relevance
“…Proteins which passed through the contact formed thick deposited films on the metallic surface. This observation is supported by other 3 studies [13][14][15] which reported thick protein deposits on joint surfaces after in vitro and in vivo (explant) use. It is usually suggested that these films act as a protective surface layers reducing adhesion and wear [15].…”
Section: Introductionsupporting
confidence: 83%
“…Proteins which passed through the contact formed thick deposited films on the metallic surface. This observation is supported by other 3 studies [13][14][15] which reported thick protein deposits on joint surfaces after in vitro and in vivo (explant) use. It is usually suggested that these films act as a protective surface layers reducing adhesion and wear [15].…”
Section: Introductionsupporting
confidence: 83%
“…The use of saline resulted in the highest wear rate of 0.89 ± 0.08 and 1.23 ± 0.07 mm 3 /Mc (Groups 4 and 5, respectively). The higher wear rate for Group 4 was expected, given that saline lacks any lubricating proteins [30], and yielded the opposite result of polymer on metal articulations [17,18]. Given the lack of evidence for third body wear from the imaging assessment for Group 5 as compared to Group 4, it is believed that slow dissolution of the coating and/or physical removal of the HA coating during specimen handling during testing is responsible for the difference in mass loss; the cycle intervals were decreased to minimize handling of the coated devices.…”
Section: Discussionmentioning
confidence: 88%
“…For example, an increase in the sliding distance a bearing surface travels can result in increased wear [15,16]. Decreasing the quantity of protein in the lubricant can increase the wear rate of UHMWPE on CoCr and decrease the wear rate of PTFE on CoCr, but testing both in a zero protein fluid yields unrealistically low wear rates for both as compared to clinical retrieval analyses [17,18]. In addition, multidirectional or ''cross-shear'' motion can increase the wear rate by an order of magnitude [19][20][21][22] or not have an effect at all [23].…”
Section: Discussionmentioning
confidence: 99%
“…Joint simulator studies have been performed for decades but there are often large differences between labs in the properties of the lubricants used to conduct the tests [42,[57][58][59]. The conditions that these simulations are run under also differ markedly from joint function in vivo including the volume and temperature of the fluids.…”
Section: Discussionmentioning
confidence: 99%